Higher order spectra analysis for assessing stationarity - Stavorovsky, Konstantin; Popov, Anton (Видавництво Львівської політехніки, 2013)
In this paper the new approach to investigation of signals stationarity based on parameters of bispectrum is proposed. The method was examined using simulated test signals artificially test signals with predefined nonstationarities. As test signals Gaussian noise with varying variance and mean value were proposed. Proposed bispectral characteristics are different for stationary and nonstationary signals.
Keywords: higher order spectra analysis; bispectrum; stationarity; parameters of bispectrum; Gaussian noise